Transformation of Myanmar Muslim community: Singapore as a role-model - U Tun Aung, Maulana Akbar Shah; Abdul Razak, Mohd Abbas; Ali, Mohammed Farid (Routledge, 2019)
This study looks into Myanmar and Singapore, holding the latter as the role model for the former. Even though both countries are homelands to minority Muslims, the situation of Muslims and other minority groups in Myanmar is not as contented as that of the Muslims in Singapore. Singapore has upheld the religion and Asian values despite her achievements in modern developments. Singapore’s steps towards maintaining racial harmony within the minority groups and between government and the minorities can be emulated by Myanmar. Through qualitative analysis of the historical accounts and library materials, the paper unveils that the present plight of the Muslims and the Rohingya like minorities in Myanmar only started with the coming of military junta into power in 1962. Racial and nationalist movements initiated by the military government eradicated the Muslim identity depriving them from the rights of citizenship. The findings also suggest ways on how Muslims in Myanmar can ignite their dying flame of patriotism, learn to re-integrate with others and contribute towards national pride and nation building. Adding onto this analysis, the multi-religious policies of Singapore and its founder Lee Kuan Yew are analyzed from archives and media materials in order to set an example for Myanmar policy makers.